Control of spatial protection in Kauman Semarang - Suprapti, Atiek; H. Kistanto, Nurdien; E. Pandelaki, Edward; Indrosaptono, Djoko (Journal of Architecture and Urbanism, 2017)
Locality and cultural identity aspects are very important to create humane cities in the midst of globalizing world. Kauman Semarang is the city’s cultural identity which has lasted for more than three centuries. Traditionally, Kauman is a village in downtown which reflects Moslem daily live. The physical and social characteristicschange are the reaction of modernization-capitalization pressure of the downtown. The purpose of the research is to find out how Kauman adapts to the incoming pressures. The research was based on ethnographic method by combining ideographic and architectural approaches. In the end of the research, it found that there is a spatial control having protective characteristic or a control of spatial protection conducted by the community. Socioreligious values have influenced in strengthening socio-religious space that produces immaterial products associated with the community’s mentality. Meanwhile, the modernization-capitalization pressures influence the form of significantly developed business-commercial space, and their products are eventually used to support the socio-religious activities. Spatial protection strategy is an answer for the problem of modernization-capitalization pressures in downtown. This finding could be a useful input for the preservation efforts at Kauman Semarang particularly and for cities having similar problems generally.